Decision leadership empowering others to make better choices - Moore, Don A. (New Haven Yale University Press, 2022)
"Leadership doesn't look like it used to. Expanding on the lessons learned from Richard H. Thaler and Cass R. Sunstein's best-selling Nudge, this book brings together research from the behavioral sciences to demonstrate how effective leadership works. While leaders have historically been lauded for their own behaviors, attributes, and decisions, this approach ignores the leader's mission to empower others. Don A. Moore and Max H. Bazerman show how effective leadership enables everyone, not just the leader, to make wise, ethical decisions consistent with their highest values. As a result, a leader's impact becomes greater because it ripples out instead of relying heavily on him or her to play the part of heroic figure. Filled with real-life stories and examples of the structures, incentives, and systems that successful leaders have used to equip others to make decisions, this study also includes cautionary tales of the consequences of ignoring these practices
Includes bibliographical references (pages 213-237) and index.
Keywords: Leadership